A nonlinear shear-lag model applied to chemical anchors subjected to a temperature distribution. (August 2018) - Lahouar, Mohamed Amine; Pinoteau, Nicolas; Caron, Jean-François; Foret, Gilles; Mege, Romain
Abstract: Adhesive joints are increasingly used in bridges and buildings construction thanks to their high mechanical properties and their ease of implementation. However, the load transfer mechanism within adhesive joints is complex and has been the subject of several studies since 1938. Several models have been developed to quantify the stress distribution along bond joints. Nevertheless, very few models exist today to study the stress distribution in chemical anchors by taking into account the temperature effect. This paper presents a non-linear shear-lag model adapted to chemical anchors allowing predicting their stress distribution profiles and fire resistance duration for any temperature distribution. The model highlights the importance of the temperature distribution on the stress profile. The paper shows that when the anchor reaches its maximum axial force, all the elements composing the anchor provide their maximum performance at the same time.